PENGARUH BOOKLET TERHADAP TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU KELUARGA PASIEN DALAM PENCEGAHAN PENULARAN PENYAKIT TBC DI PUSKESMAS BOLANGITANG - Lakoro, Cici Nurmaya; Rahayu, Mesra; Djumadi, Djumadi; Yulis, Dian Meiliani; Rusli, Rusli (NHM PRESS, 2024)
This study aims to develop and analyze the effectiveness of booklet media as an educational tool for increasing knowledge, attitudes, and behavior of tuberculosis patients' families in preventing transmission at the Bolangitang Health Center. The research uses a development approach, utilizing the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. The subject of this research includes tuberculosis patients' families in the working area of the Bolangitang Health Center. The research steps include needs analysis, design, development of a booklet, and a pilot test to evaluate its effectiveness. Data collection techniques are through pretest and posttest questionnaires, and analysis is conducted using descriptive and inferential statistics. The study concludes that the booklet media is effective in improving knowledge, attitudes, and behavior regarding tuberculosis transmission prevention among the families of tuberculosis patients. The booklet can be a valuable tool for health education, particularly in improving community awareness and preventive actions against tuberculosis transmission.